2021
DOI: 10.1111/jce.15002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diagnosis‐to‐ablation time on non‐pulmonary vein triggers and ablation outcomes in persistent atrial fibrillation

Abstract: Introduction: Non-pulmonary vein (PV) triggers are a major cause of atrial tachyarrhythmia (ATA) recurrence after catheter ablation. However, the effect of the diagnosisto-ablation time (DAT) on non-PV triggers in persistent atrial fibrillation is unknown.Methods and Results: This observational study evaluated 502 consecutive persistent AF patients who underwent initial ablation. We compared 408 patients whose DAT was <3 years with 94 patients whose DAT was ≥3 years. Following PV and posterior wall isolation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Among 2118 de-novo ablation and 227 repeat ablations for atrial fibrillation, Kim et al [36] reported that 11.7 and 28.6% of patients were found to have extrapulmonary triggers, respectively. Factors associated with the existence of extrapulmonary triggers include age, left atrial volume, female sex, presence of diabetes, higher parasympathetic nerve activity, and longer diagnosis to ablation time [36,37]. On the premise of risk control, elimination of these triggers could be rewarding.…”
Section: Ablation For Extrapulmonary Triggersmentioning
confidence: 99%
“…Among 2118 de-novo ablation and 227 repeat ablations for atrial fibrillation, Kim et al [36] reported that 11.7 and 28.6% of patients were found to have extrapulmonary triggers, respectively. Factors associated with the existence of extrapulmonary triggers include age, left atrial volume, female sex, presence of diabetes, higher parasympathetic nerve activity, and longer diagnosis to ablation time [36,37]. On the premise of risk control, elimination of these triggers could be rewarding.…”
Section: Ablation For Extrapulmonary Triggersmentioning
confidence: 99%
“…While linear-based ablations including posterior wall isolation are uniform procedures, CFAE ablation, LVA ablation and non-PV trigger ablation may be unique treatments for each patient. Recently, it has been reported that elimination of non-PV triggers is related to favorable outcomes in persistent AF as well as in paroxysmal AF [ 11 15 ]. Although the impact of non-PV triggers in AF has become more evident, non-PV trigger ablation has not been standardized as an additional procedure to PVI, partly because of the need of skilled catheter technique of non-PV trigger mapping [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Similarly, the shorter time from the first diagnosis of persistent AF to ablation reduces the occurrence of extrapulmonary vein triggers and recurrence of atrial tachyarrhythmias. 10 In this journal, Carddoso et al 11 presented an elegant systematic review and meta-analysis on the superiority of catheter ablation as first-line therapy over AADs for AF.…”
mentioning
confidence: 99%